2004
DOI: 10.1038/ni1099
|View full text |Cite
|
Sign up to set email alerts
|

B cell–specific loss of histone 3 lysine 9 methylation in the VH locus depends on Pax5

Abstract: Immunoglobulin heavy chain rearrangement (V H -to-DJ H ) occurs only in B cells, suggesting it is inhibited in other lineages. Here we found that in the mouse V H locus, methylation of lysine 9 on histone H3 (H3-K9), a mark of inactive chromatin, was present in non-B lineage cells but was absent in B cells. As others have shown that H3-K9 methylation can inhibit V(D)J recombination on engineered substrates, our data support the idea that H3-K9 methylation inhibits endogenous V H -to-DJ H recombination. We also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
99
5

Year Published

2005
2005
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(113 citation statements)
references
References 55 publications
7
99
5
Order By: Relevance
“…For the V H 81X gene, as previously reported by Johnson et al (2004), we found that the CpG site at position +143 (relative to the start of the coding region) was methylated in all clones analyzed, whereas the second site (+196) was partially methylated (62% of all clones, Fig. 4D).…”
Section: Binding Of Pax5 To Individual V H S107 Family Members Correlsupporting
confidence: 86%
See 4 more Smart Citations
“…For the V H 81X gene, as previously reported by Johnson et al (2004), we found that the CpG site at position +143 (relative to the start of the coding region) was methylated in all clones analyzed, whereas the second site (+196) was partially methylated (62% of all clones, Fig. 4D).…”
Section: Binding Of Pax5 To Individual V H S107 Family Members Correlsupporting
confidence: 86%
“…Because it has been proposed that removal of H3/K9me2, a maker of repressive chromatin, seems to be required to promote V H-to-DJ H rearrangements (Johnson et al, 2004), we tested the hypothesis that H3/K9me2 was preferentially removed from highly rearranging V H genes but not from poorly rearranging V H genes. Indeed, we find that in pro-B cells, poorly rearranging V H genes show higher association with H3/K9me2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations